The Effect of Bifurcated Geometry on the Diodicity of Tesla Valves - Sean Wiley; Huei-Ping Huang (Fluids)
The Tesla valve is a fluidic diode that enables unidirectional flow while impeding the reverse flow without the assistance of any moving parts. Conventional Tesla valves share a distinctive feature of a bifurcated section that connects the inlet and outlet. This study uses computational fluid dynamic (CFD) simulations to analyze the importance of the bifurcated design to the efficiency of the Tesla valve, quantified by diodicity. Simulations over the range of the Reynolds number, Re = 50–2000, are performed for three designs: the T45-R, D-valve, and GMF valve, each with two versions with and without the bifurcated section. For the T45-R valve, removing the bifurcated section leads to a consistent increase in diodicity, particularly at high Re. In contrast, the diodicity of the GMF valve drops significantly when the bifurcated section is removed. The D-valve exhibits a mixed behavior. Without the bifurcated section, its diodicity is suppressed at low Re but begins to increase for Re > 1100, eventually matching the diodicity of the bifurcated version at Re = 2000. The results highlight the intricate relationship between valve geometry and efficiency of Tesla-type valves and the dependence of this relationship on the Reynolds number.